دور السياسة الجزائرية في مواجهة التهديدات الأمنية بعد 2011 - مسكين, أحمد (جامعة الوادي University of Eloued, 2019)
" تناولت الدراسة محاولة فهم توجّه السياسة الجزائرية، خاصة في شقها الأمني بالنظر إلى جملة التهديدات الأمنية، التي لا تزال تواجهها الجزائر خاصة في ظل موقعها الجيوسياسي ضمن بيئة إقليمية متدهورة بشكل كبير، إرتبطت بالتغيرات السياسية و الأمنية التي شهدتها الساحة العربية و الإفريقية، إضافة إلى الوضع الداخلي للجزائر و الحاجة الملحة للتنمية في كافة الميادين السياسية و الإقتصادية و الإجتماعية...إلخ، مع وجود محاولات للخروج من هذه الوضعية الصعبة بالبحث عن حلول سياسية و إقتصادية و دبلوماسية ناجعة، وكذا السعي لتحقيق أبعاد الأمن للوصول إلى مفهوم الأمن الإنساني، الذي برز بتعدد و تنوع التهديدات الأمنية، و تجاوز مفهوم الأمن التقليدي، القائم على تحقيق قوة الدولة و حماية حدودها عسكريا. كما أن للبيئة الإقليمية للدول المجاورة للجزائر منذ سنة 2011، أثر كبير في تزايد الوعي الأمني للجزائر، من خلال تطبيق إستراتيجية متكاملة ، تعمل على تعزيز الإستقرار الداخلي سياسيا و إقتصاديا و أمنيا، بالتركيز على الدبلوماسية خارجيا، و التأكيد على ضرورة إتباع الوسائل السلمية في حل النزاعات و تجاوز الأزمات خاصة بدول الجوار، مع التصدي للإرهاب و كافة أشكال الجريمة المنظمة على رأسها عمليات التهريب و تجارة المخدرات. " "The study delt with an attempt to understand the direction of algerian politics, especially from the scurity threats that algeria is still facing in view of its geo-political position within a deeply deteriorating regional environment. It has been linked to the political and security changes witnessed in the arab and African regions, and the need of the development in all political, economic, social fields,ect…, with attempts to get out of this difficult situation by seeking political, economic and diplomatic solutions. As well as seeking to achieve security dimensions to reach the concept of human security, Which has emerged multiple security threats and exceed the concept of traditional security based on achievement of the power of the state and protect its borders militarily. The regional environment of the neighboring countries of Algeria since 2011, has greatly increased the security awareness of Algeria through the Implementation of an integrated strategy that promotes internal stability politically, economically and security by focusing on external diplomacy and emphazing the need to adopt peaceful means to resolve disputes and overcome crises, especially in neighboring countries While dealing with terrorism and all forms of organized crime, mainly trafficking and drug trafficking. "
ماستر سياسة عامة
Keywords: السياسة الجزائرية ، التهديدات الأمنية ، دور السياسة الجزائرية; Algerian politics, security threats, the role of Algerian politics